Effects of mGluR5 and mGluR1 antagonists on anxiety-like behavior and learning in developing rats - Mikulecká, Anna; Mares, Pavel (Behavioural brain research, 2009)
Antagonists of group I metabotropic receptors exhibit anxiolytic action in adult rats. In immature animals we demonstrated anticonvulsant action of MPEP and AIDA, antagonists of group 5 and group 1, respectively. However, there are no developmental data on anxiolytic-like and learning actions of both compounds. This study investigated whether the anticonvulsant dose range of MPEP and AIDA affects anxiety-like behavior and learning ability in immature rats. Animals at 12, 18 and 25 postnatal (P) days received MPEP in doses of 10, 20 or 40 mg/kg i.p., AIDA in doses of 10 or 20 mg/kg i.p. In P18 and P25 rats anxiety-like behavior and locomotor activity were tested in the light-dark box and open-field test at 15 (1st session) and 60 (2nd session) minutes after drug administration. Learning ability of P12, P18, and P25 animals was examined in the homing response test 15 min after drug administration. Both antagonists exhibited anxiolytic-like action in the 1st session, effects in the 2nd session were less marked. In the open-field test both antagonists increased locomotion only in P18 animals. Age-dependent changes were found in the homing response test, the return latency being longer only in P12 animals. While MPEP in doses of 20- and 40-mg/kg in P12 and 40-mg/kg in P18 rats prolonged the homing response, AIDA did not affect the homing behavior. Both MPEP and AIDA exert anxiolytic-like effect also in immature rats. Except for the youngest animals no changes in learning ability in the homing response test were found.
Keywords: Animals; pyridiny; Anti-Anxiety Agents; Rats, Wistar; učení; Neuropsychological Tests; Excitatory Amino Acid Antagonists; úzkost; Aging; pohybová aktivita; časové faktory; Time Factors; neuropsychologické testy; receptory metabotropního glutamátu; metabotropní glutamátové receptory podtypu 5; anxiolytika; Anxiety; Learning; Receptor, Metabotropic Glutamate 5; Male; Indans; Pyridines; stárnutí; Receptors, Metabotropic Glutamate; krysa rodu Rattus; Motor Activity; Random Allocation; zvířata; mužské pohlaví; indany; Rats; náhodné rozdělení; antagonisté excitačních aminokyselin; potkani Wistar